Infiltrasi Nalar Ideologis dalam Tafsīr Lugawī: Kritik Jamāl Muṣṭafā al-Najjār terhadap Interpretasi Al-Qur’an Berbasis Kaidah Bahasa - Wafiudin, M. Afif; Riyadi, Abdul Kadir; Hakim, Muhammad Naufal (UIN Syarif Hidayatullah Jakarta, 2024)
The linguistic approach in interpreting the Qur’an is considered an ideal approach. However, in practice, this approach is often used as a tool for ideological infiltration. Based on this, this research focuses on examining linguistic interpretation and attempts to identify the aspects and types of ideological infiltration in linguistic exegesis by adhering to the systematic critique of al-Najjār. This research employs content analysis methods based on the theory of the muwāfaqah al-lughah wa al-sharī‘ah. The findings of this research indicate that to assess whether linguistic exegesis is ideologically infiltrated or not, one can see to what extent the interpretation aligns with linguistic and sharia principles. Additionally, according to al-Najjār, there are three forms of ideological infiltration in linguistic exegesis, through naḥw, the literal meaning of words, and qirā’at of the Qur’an.